2012
DOI: 10.1182/blood-2011-10-384057
|View full text |Cite
|
Sign up to set email alerts
|

Induction of acute GVHD by sex-mismatched H-Y antigens in the absence of functional radiosensitive host hematopoietic–derived antigen-presenting cells

Abstract: IntroductionAg presentation on radiosensitive host hematopoiesis-derived APCs to the alloreactive donor T cells is considered to be obligatory for the induction of acute GVHD. 1-9 However, under certain conditions, whether clinically relevant minor Ags can induce GVHD in the absence of functional radiosensitive host hematopoietic APCs is not known. [6][7][8]10 Clinical data from MHC-matched BMT show that male recipients from female donors (F3M) are at a greater risk of developing GVHD 9 and show H-Y-specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 46 publications
2
79
0
1
Order By: Relevance
“…T cells transplanted from adult female donors can be activated by exposure to Y-chromosome-associated proteins and may cause chronic GVHD, but those from female U-CB units may be less activated against them. 31 Studies on the effect of the CMV Ab on chronic GVHD development have previously yielded controversial results. 2,32 In this study, we observed a significant impact of CMV seropositivity on the incidences of chronic GVHD and extensive chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…T cells transplanted from adult female donors can be activated by exposure to Y-chromosome-associated proteins and may cause chronic GVHD, but those from female U-CB units may be less activated against them. 31 Studies on the effect of the CMV Ab on chronic GVHD development have previously yielded controversial results. 2,32 In this study, we observed a significant impact of CMV seropositivity on the incidences of chronic GVHD and extensive chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Recent data have indicated that both host hematopoietic or nonhematopoietic APCs, in the absence of one or another, can activate donor T cells and induce GVHD. 18,19,21 Furthermore, the elimination of specific hematopoietic APC subsets, such as DCs or macrophages, may aggravate GVHD, suggesting that these cells may play a role in controlling GVHD. 18,20,22,44 These observations, taken in light of our data, suggest that the negative regulatory pathways of professional APCs, DCs, or macrophages, might be critical for reducing GVHD severity following its induction by the activation of donor T cells by the DAMP/PAMP activated host APCs.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly critical in light of the recent observations, which demonstrate that the absence of any one subset of professional host-derived hematopoietic APCs, such as DCs or macrophages, contrary to the expectations of reducing donor T-cell responses, are either irrelevant, or actually enhance donor T-cell responses and accentuate GVHD severity. [18][19][20][21][22] These newer observations suggest that pathways that mitigate the hematopoietic APCs may be as critical for attenuating GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…FACS analyses were performed as previously described (38,39). Briefly, to analyze donor T cell expansion and activation markers, splenocytes from transplant-recipient mice were resuspended in FACS wash buffer (2% BSA in PBS) and stained with the following conjugated mAbs: PerCP-Cy5.5-conjugated mAbs against mouse CD4 (clone GK1.5) and CD8 (clone 53-6.7); PE-conjugated mAbs against mouse CD69 (clone H1.2F3), CD183 (CXCR3) (clone CXCR3-173), LPAM-1 (integrin α4β7) (clone DATK32), CD62L (clone MEL-14), and TIGIT (clone 1G9); APC-conjugated mAbs against mouse H-2K b (clone AF6-88.5), CD44 (clone IM7), PD-1 (clone 29F.1A12), and Lag3 .…”
Section: Methodsmentioning
confidence: 99%